It is not only size that matters: How unique is the Estonian e-governance success story? - Fabian Stephany (Agenda Austria, 2018)
User data fuel the digital economy, while individual privacy is at stake. Governments react differently to this challenge. Estonia, a small Baltic state, has become a role model for the renewal of the social contract in times of big data. The Estonian example suggests that online governance is most successful in a small state, with a young population, trustworthy institutions and the need of technological renewal. This work examines the development of e-governance usage during the last decade in Europe from a comprehensive cross-country perspective: Size, age and trust are relevant for the development of digital governance in Europe. However, the quality of past communication infrastructure is not related to e-governance popularity.
Keywords: 330; E-Governance; Europe; Estonia; Random Model; Trust